Capacity Building of Volunteer Team to Support Smoking Cessation in Navigation Area, Na Wong Sub-district, Huai Yot District, Trang Province, Thailand - ชูสกุล, สุมลรัตน์ (Journal of Health Science of Thailand, 2022)
The objective of this study was to develope capacity of a volunteer team assist help smoking cessation program in Huai Yot Hospital, Trang Province, in order to achieve high proportion of smoking cessation in the community. The volunteer team was selected from the village health volunteers in the area and had intention to help smokers quit smoking. The volunteers were strengthen on their capacity through knowledge and skills training on smoking cessation. The project was started in Na Wong Subdistrict, Huai Yot District, Trang Province, begining with recruitment of people who volunteered to quit smoking. The volunteer team began to develop a media campaign, and create innovations to use as a medium for campaigning smoking cessation activities inthe community; and follow-up with the smokers on their smoking behaviours. It was found that among 100 smokers participated in the program in the year 2018, 70% of them were able to quit smoking. The outcome was higher then that of the years 2016 and 2017 of which the cessation rate was 40.0% and 33.3%, respectively.